2020
DOI: 10.1038/s41598-020-73045-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring cyclic networks of multisite modification reveals origins of information processing characteristics

Abstract: Multisite phosphorylation (and generally multisite modification) is a basic way of encoding substrate function and circuits/networks of post-translational modifications (PTM) are ubiquitous in cell signalling. The information processing characteristics of PTM systems are a focal point of broad interest. The ordering of modifications is a key aspect of multisite modification, and a broad synthesis of the impact of ordering of modifications is still missing. We focus on a basic class of multisite modification ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…Networks of cyclic phosphorylation have been studied in Suwanmajo et al. ( 2020 ). The authors study in particular the following mass action network ( 1 ) derived from the reaction scheme of Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Networks of cyclic phosphorylation have been studied in Suwanmajo et al. ( 2020 ). The authors study in particular the following mass action network ( 1 ) derived from the reaction scheme of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 a and , , and denote enzyme-substrate complexes): Suwanmajo et al. ( 2020 ) it is shown that for every admissible positive value of the total concentrations and all positive values of the reaction rate constants there exists a unique positive steady state. The authors furthermore provide parameter values where a Hopf bifurcation occurs (with the total amount of kinase as a bifurcation parameter) and sustained oscillations emerge (Suwanmajo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation